SUGARCANE AND DROUGHT IN NORTHEASTERN BRAZIL: AN ECOCRITICAL ANALYSIS OF THE WORK O QUINZE, BY RACHEL DE QUEIROZ (CIPEEX, 2022)
THE PRESENT WORK AIMS TO ANALYZE THE PRESENCE OF THE SUGARCANE CULTURE AND ITS IMPACTS ON THE ENVIRONMENT, FROM HISTORICAL AND LITERARY PERSPECTIVES, WITHIN THE WORK "O FIFTEEN" BY BRAZILIAN AUTHOR RAQUEL DE QUEIROZ. CONSIDERING THE CONCERNS AND ANXIETIES AT THE TIME RELATED TO CLIMATE CHANGE AT THE LOCAL LEVEL AND THE PROCESS OF DESERTIFICATION IN BRAZIL. IDENTIFYING THE STRENGTH OF SUGARCANE AS A MOBILIZING AGENT OF THE INTELLECTUAL DEBATE ABOUT DROUGHT AND THE PROCESS OF DESERTIFICATION IN BRAZIL, AS WELL AS UNDERSTANDING THE SUBJECTIVE DESIRES AND CONCERNS PRESENTED IN THE CHARACTERS OF THE WORK IN RELATION TO THIS WHOLE CONTEXT OF ENVIRONMENTAL APOCALYPSE. THE RESEARCH IS QUALITATIVE, AIMING AT A DOCUMENTAL ANALYSIS THROUGH LITERATURE, ADOPTING THE METHODS AND APPROACHES OF ECOCRITICISM, WHICH WILL ENABLE THE UNDERSTANDING OF THE ECOCENTRIC ELEMENTS IN THE WORK, AS MOBILIZERS OF FEELINGS, DESIRES AND POSSIBILITIES, THEREFORE, THE STRENGTH OF AN ELEMENT NON-HUMAN, SUGARCANE, AS THE MAIN AGENT IN SOCIOCULTURAL INTERMEDIARIES.&NBSP;KEYWORDS:ECOCRITICISM; ENVIRONMENT; CLIMATE CHANGES; DESERTIFICATION.
Keywords: Ecocrítica; Meio Ambiente; Mudanças Climáticas; Desertificação.